2021
DOI: 10.3390/ani11010168
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Population Structure of Wild Pigs in Southern Texas

Abstract: Wild pigs (Sus scrofa) alter ecosystems, affect the economy, and carry diseases that can be transmitted to livestock, humans, and wildlife. Understanding wild pig movements and population structure data, including natural population boundaries and dispersal, may potentially increase the efficiency and effectiveness of management actions. We trapped, conducted aerial shootings, and hunted wild pigs from 2005 to 2009 in southern Texas. We used microsatellites to assist large-scale applied management. We quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…In the absence of welldefined genetic structure, it is possible that individuals are moved hundreds of kilometers and yet are still sampled within the spatial extent of the same broad cluster. A recent study restricted to wild pigs in southern Texas revealed similar patterns of highly admixed populations, which was attributed to multiple introductions and anthropogenic movement (Delgado-Acevedo et al 2021). Our preliminary isolation by distance analysis (Fig.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In the absence of welldefined genetic structure, it is possible that individuals are moved hundreds of kilometers and yet are still sampled within the spatial extent of the same broad cluster. A recent study restricted to wild pigs in southern Texas revealed similar patterns of highly admixed populations, which was attributed to multiple introductions and anthropogenic movement (Delgado-Acevedo et al 2021). Our preliminary isolation by distance analysis (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…These vast areas of admixed and spatially dispersed clusters create additional challenges. For example, the control of a foreign animal disease upon introduction in a weakly resolved, spatially dispersed genetic cluster would necessitate the coordination of management action across an extensive area (Brown et al 2020, Delgado-Acevedo et al 2021. With genetic patterns demonstrating high rates of connectivity throughout and among these spatially dispersed clusters, policies are needed to limit anthropogenic movement and remove economic incentives that encourage the translocation and release of wild pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a set of microsatellite markers was developed for swine biodiversity applications (Committee 2004). The usefulness of these microsatellite markers has been veri ed by numerous population genetic studies of wild boars (Costa et al 2012;Choi et al 2014;Delgado-Acevedo et al 2021). Dispersal distance estimation with kinship analysis using polymorphic markers has been reported previously for several species (Cayuela et al 2018).…”
Section: Introductionmentioning
confidence: 94%
“…On the other hand, population structure studies can inform management decisions to control the damage caused by feral and wild pigs (Delgado-Acevedo et al, 2021;Hampton et al, 2004). In this study, we explored the genetic diversity and population structure of the PhNP to inform conservation.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, genetic diversity and structure analysis of the Iberoamerican livestock breeds justified the recognition of the Creoles breed of livestock and therefore subsequent conservation programs (Gama et al., 2020 ). On the other hand, population structure studies can inform management decisions to control the damage caused by feral and wild pigs (Delgado‐Acevedo et al., 2021 ; Hampton et al., 2004 ). In this study, we explored the genetic diversity and population structure of the PhNP to inform conservation.…”
Section: Introductionmentioning
confidence: 99%